2005
DOI: 10.1044/1092-4388(2005/040)
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory Complexity, Ambient Frequency, and Functional Load as Predictors of Consonant Development in Children

Abstract: The notion of a universal pattern of phonological development, rooted in basic physiological constraints, is controversial, with some researchers arguing for a strong environmental (ambient language) influence on phonological development or an interaction of both physiological constraints and ambient language effects. This research examines the relative value of articulatory complexity, ambient frequency, and functional load as predictors of consonant development in children. Three languages are investigated: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 27 publications
1
52
1
2
Order By: Relevance
“…Although CAoA typically has been associated with articulatory complexity (e.g., Kent, 1992;Stokes & Surendran, 2005), a purely articulationbased view of the CAoA effect seems to be inconsistent with both the findings reported here and previous work examining articulatory and motoric demands in NWR performance (e.g., Archibald et al, 2013;Archibald & Gathercole, 2006;Edwards & Lahey, 1998). In the current study, the CAoA effect persisted across lexical-access tasks that minimized articulatory, short-term-memory, and auditory-perceptual demands.…”
Section: Caoa Reflects a Central Level Of Phonological Representationcontrasting
confidence: 56%
See 3 more Smart Citations
“…Although CAoA typically has been associated with articulatory complexity (e.g., Kent, 1992;Stokes & Surendran, 2005), a purely articulationbased view of the CAoA effect seems to be inconsistent with both the findings reported here and previous work examining articulatory and motoric demands in NWR performance (e.g., Archibald et al, 2013;Archibald & Gathercole, 2006;Edwards & Lahey, 1998). In the current study, the CAoA effect persisted across lexical-access tasks that minimized articulatory, short-term-memory, and auditory-perceptual demands.…”
Section: Caoa Reflects a Central Level Of Phonological Representationcontrasting
confidence: 56%
“…Evidence against this explanation is demonstrated in work showing that frequency of phoneme occurrence in English does not account for significant variance in the emergence or mastery of consonant sounds (Mader, 1954;Mines, Hanson, & Shoup, 1978;Stokes & Surendran, 2005). Further, a significant effect of CAoA has been observed in college students (Moore et al, 2010), whereas the phonotactic-probability manipulation has been shown to attenuate with age (Munson, 2001).…”
Section: Alternative Explanations For the Caoa Effectmentioning
confidence: 90%
See 2 more Smart Citations
“…Tjaden and Sussman (2006) provided evidence for integrated speech perception theories, showing that listeners were tuned to similar types of coarticulatory information in speech produced by speakers with Parkinson's disease or multiple sclerosis, or normal speakers. Finally, as previously mentioned, Stokes and Surendran (2005) have demonstrated that articulatory complexity plays a primary role in determining the route and age of phoneme acquisition for normally-developing children. Together with their finding, the current study provides evidence of a key characteristic shared by dysarthric speech and normal speech at the motor execution stage of the utterance: i.e., sounds requiring fine, complex control of the articulators are more likely to be misarticulated in both dysarthric speech and the speech of normally-developing children during phonological acquisition.…”
Section: Discussionmentioning
confidence: 85%